The [Rh(Xantphos)]+ catalyzed hydroboration of diphenylacetylene using trimethylamine-borane - Dietz, M; Johnson, A; Martínez-Martínez, A; Weller, A (Elsevier, 2019)
The rhodium(I) complex [Rh(κ3-P,O,P-Xantphos)(η2-PhC≡CPh)][BArF4] (ArF = 3,5-(CF3)2C6H4) is an effective catalyst for the cis-selective hydroboration of the alkyne diphenylacetylene using the amine-borane H3B·NMe3. Detailed mechanistic studies, that include initial rate measurements, full simulation of temporal profiles for a variety of catalyst and substrate concentrations, and speciation experiments, suggest a mechanism that involves initial coordination of alkyne and a saturation kinetics regime for amine-borane binding. The solid-state molecular structure of a model complex that probes the proposed resting state is also reported, [Rh(κ3-P,O,P-Xantphos)(NCMe)(η2-PhC≡CPh)][BArF4].